Funding Philanthropy for PAUD Wadas Kelir Purwokerto - Bayu Santo Nugroho; Akhmad Faozan; Mukhamad Hamid Samiaji (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2022)
Research on philanthropy for financing educational institutions aims to find out about how the philanthropy of financing is carried out at PAUD Wadas Kelir Purwokerto. This research is included in qualitative descriptive research with a case study method. Data collection techniques were obtained through observation (researchers went directly to the PAUD Wadas Kelir institution), interviews (to principals and parents) and documentation (learning activities, activity programs, school financing sources). The results of this study show that the philanthropy of financing educational institutions in PAUD Wadas Kelir carried out by the community also supports learning activities so that the PAUD Wadas Kelir institutions have survived until now.  The existence of this institutional financing philanthropy is very helpful in improving the quality of learning, completing school facilities, and improving the quality of early childhood education.